A 'one pot' gel combustion strategy towards Ti3+ self-doped 'black' anatase TiO2−x solar photocatalyst. Issue 16 (11th April 2016) - Ullattil, Sanjay Gopal; Periyat, Pradeepan
Abstract : The first one pot gel combustion synthetic strategy towards 'black TiO2− x ' using Ti butoxide, diethylene glycol and water as the only precursors. Abstract : A one pot gel combustion synthetic strategy has been developed for the first time towards the rapid formation of self-doped black anatase TiO2− x (BAT) using titanium butoxide, diethylene glycol (DEG) and water as the only precursors. This swiftly formed nanoplatform was occupied with a high concentration of surface defect sites, especially Ti 3+ and oxygen vacancy sites in excess. The in (lattice) and out (surface) defect states were confirmed by Raman, XPS and TEM analysis. These defect-enriched features enabled 33% more photocatalytic activity for BAT than the commercially available photocatalyst Degussa-P25 under solar illumination.